Research hotspots and trends in sustainable development goals - Guofeng Wang; Baohui Zhao (Environmental and Sustainability Indicators)
The Sustainable Development Goals (SDGs) serve as a globally recognized framework for countries to eradicate poverty, protect the environment, and promote global economic, social, and technological progress in harmony with nature. This study conducts a quantitative literature analysis of 21,076 SDG-related articles indexed in the Web of Science from 2003 to 2024 to assess the evolution of and gaps in research on the SDGs. It also extends the analysis by examining trends in SDG research post-COVID pandemic. The main findings include the following: (1) The SDGs most extensively investigated were SDG 13 (Climate Action), SDG 3 (Good Health and Well Being), and SDG 11 (Sustainable Cities and Communities), collectively accounting for 36.45 % of the mapped studies. In stark contrast, the combined share of research on SDG 4 (Quality Education), SDG 10 (Reducing Inequality), SDG 17 (Partnerships For The Goals), and SDG 16 (Peace And Justice Strong Institutions) is only 3.79 % of the mapped studies. (2) Research output on the SDGs is growing exponentially, with the US, UK, and China accounting for 46.81 % of publications, indicating geographical concentration. (3) At present, research is mainly focused on SDG 13 (Climate action), SDG 3 (Health), and SDG 11 (Sustainable Cities). There are many overlaps in interdisciplinary research, and significant progress has been made in emerging areas such as sustainable finance, bio-agriculture, and health system innovation. The analysis identified three key paths for future research: first, promoting low-carbon transformation through multi-institutional cooperation; second, integrating remote sensing into smart decision-making systems for urban and rural development; and third, systematically studying the synergistic effects of the SDGs while addressing the targets that have not been sufficiently studied.